PENGARUH PENGGUNAAN TEPUNG JAHE (ZINGIBER OFFICINALE) DALAM RANSUM TERHADAP PERTUMBUHAN AYAM KAMPUNG - Ayunin, Qurota; Y.Tantu, Rizal (AgriSains, 2012)
Ginger (Zingiber officinale) contains 1-4% volatile oil and oleoresin. Essential oil helps the digestive enzymes to digest feed that increase passage rate of digest this increase feed intake. The increase in feed consumption leads to enhance growth and meet production. A study was conducted in the Department of Animal Husbandry, Faculty of Animal Husbandry and Fisheries, University Tadulako Palu, from May 9th to August 8th, 2012. A total of 60 village chickens (two weeks old) was obtained from CV. Black Horse Perkasa, Kediri, and placed in 20 cage, cage size was 60 x 60 x 85 cm each cage was equipped with drinking and feed container. This research used Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments tested were as follows: R0 = no added flour ginger in the ration, R1 = 99.5% with 0.5% added ginger powder, R2 = 99% supplemented with 1% ginger powder, and R3 = 98.5% added with 1.5% ginger powder. The results of the analysis indicate that the use of a variety of ginger powder in the ration produced a significant influence (P <0.01) on ration consumption, body weight gain and feed conversion ratio. The conclusion of this study that the addition of ginger powder in chicken rations provide a very real effect on ration consumption, body weight gain and conversion ratio. R1 treatment (0.5% ginger powder in the ration) is the best treatment, because it can increase body weight gain, reduce consumption and conversion ratio. Key words : Chicken Village, Ginger Wheat, Growth, Consumption, Feed Conversion